Student's awareness towards factor affecting oral cancer in UiTM Kota Bharu, Kelantan / Awanis Anwar, Noor Afifah Ahmad and Wan Haszuliyanty Afieka Wan Zulkifly - Anwar, Awanis; Ahmad, Noor Afifah; Wan Zulkifly, Wan Haszuliyanty Afieka (2018)
Oral cancer is a disease that can occur in the surrounding of the mouth. Oral cancer become one of most serious cancer in most of countries and can cause death. The aim of this study was to identify the knowledge level of general awareness of oral cancer between students in UiTM Kota Bharu, Kelantan. Four variables were included in the study including demographic profile, knowledge of signs or symptoms of oral cancer, knowledge of risk factors of oral cancer and habits. The researcher designed the questionnaire based on the literature and expert opinions. The items on the questionnaire developed for this study were divided into five sections which are demographic profile, general awareness of oral cancer, knowledge of signs or symptoms of oral cancer, knowledge of risk factors of oral cancer and habits. Related variable was determined using Pearson's Correlation for signification relationship between dependent variable and independent variable. The factor significant that influence between variable are using multiple linear regression. For demographic profile, the researcher used the demographic analysis. The researcher also done the reliability test for all variable involve except for demographic profile. In conclusion, all three variables, (knowledge of signs or symptoms of oral cancer, knowledge of risk factors of oral cancer and habits) are significant to the general awareness of oral cancer among students in UiTM Kota Bharu, Kelantan.